2012
DOI: 10.1103/physrevb.85.214528
|View full text |Cite
|
Sign up to set email alerts
|

Bimagnon studies in cuprates with resonant inelastic x-ray scattering at the OKedge. II. Doping effect in La2xSrx<

Abstract: We present RIXS data at the O K edge from La 2−x Sr x CuO 4 vs doping between x = 0.10 and x = 0.22 with attention to the magnetic excitations in the mid-infrared region. The sampling done by RIXS is the same as in the undoped cuprates provided the excitation is at the first prepeak induced by doping. Note that this excitation energy is about 1.5 eV lower than that needed to see bimagnons in the parent compound. This approach allows the study of the upper region of the bimagnon continuum around 450 meV within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…This feature can be attributed to bimagnons, because (1) their energy scales are consistent with the bimagnons (160 meV for Sr 2 IrO 4 and 185 meV for Sr 3 Ir 2 O 7 ) measured by Raman scattering [47] and (2) their dispersions are in agreement with those measured by Ir L 3 RIXS [16][17][18]. Note that the bimagnons of cuprates measured by O K RIXS are nondispersive [35,36]. The presence of both single magnons and bimagnons indicates that O K RIXS is a powerful spectroscopic method for studying the magnetic dynamics of iridates.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This feature can be attributed to bimagnons, because (1) their energy scales are consistent with the bimagnons (160 meV for Sr 2 IrO 4 and 185 meV for Sr 3 Ir 2 O 7 ) measured by Raman scattering [47] and (2) their dispersions are in agreement with those measured by Ir L 3 RIXS [16][17][18]. Note that the bimagnons of cuprates measured by O K RIXS are nondispersive [35,36]. The presence of both single magnons and bimagnons indicates that O K RIXS is a powerful spectroscopic method for studying the magnetic dynamics of iridates.…”
supporting
confidence: 72%
“…Therefore, soft x-ray RIXS is a promising method for studying artificial two-dimensional samples [7,8]. However, given that SOC is absent in the O 1s level, O K RIXS is expected to be insensitive to single spin-flip excitations [31,35,36]. This would severely limit the applicability of O K RIXS on iridates and related 5d TM oxides, especially thin films and heterostructures fabricated by these materials, where magnetic excitations need to be studied for probing the low-energy Hamiltonian [15][16][17][18].…”
mentioning
confidence: 99%
“…[34][35][36][37]54,55] in the case of the Heisenberg model, consistent with our UCL expansions for the Hubbard and t − J models. Note that usually the Green's functions containing the two-spin and the threespin operators are referred to as probing the "two-magnon" and the "three-magnon" spectrum, though this terminology may be used loosely in this context.…”
Section: Appendix B: Ucl Approximation For the T − J Modelsupporting
confidence: 63%
“…The fast collision approximation [28][29][30] and the effective operator approach [31] suggested that only single magnon excitations or Sðq; ωÞ should be measured by RIXS at the Cu L edge [27,31,32]. More sophisticated treatments-the ultrashort core-hole lifetime (UCL) expansion [33][34][35] and the UCL-inspired ansatz [36]-highlighted that RIXS should also be sensitive to bimagnon excitations. A further extension of UCL also pointed out the importance of three-magnon excitations [37].…”
Section: When ∼10mentioning
confidence: 99%
“…bi-magnon) scattering -are allowed [17][18][19]. Indeed bi-magnon scattering is observed both at TM [20,21] and oxygen (O) K-edges [22,23]. This apparent absence of single-magnon spin-flip scattering is unfortunate because the O K-edge is in a soft x-ray regime where the RIXS resolution is particularly high (even if in this situation only a limited part of momentum space is accessible) and oxygen anions are obviously ubiquitous in magnetic materials.…”
mentioning
confidence: 99%